Bitter - Emezi, Akwaeke (Alfred A. Knopf, 2022)
"After a childhood in foster care, Bitter is thrilled to have been chosen to attend Eucalyptus, a special school where she can focus on her painting surrounded by other creative teens. But outside this haven, the streets are filled with protests against the deep injustices that grip the city of Lucille. Bitter's instinct is to stay safe within the walls of Eucalyptus but her friends aren't willing to settle for a world that's so far away from what they deserve. Pulled between old friendships, her artistic passion, and a new romance, Bitter isn't sure where she belongs--in the studio or in the streets. And if she does find a way to help the revolution while being true to who she is, she must also ask: at what cost?"--